2018
DOI: 10.1163/1568539x-00003491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nestlings’ age on parental responses to a predatory snake in Parus minor

Abstract: Predator-specific alarm calls may have a variety of context-specific functions. Parents of the oriental tit,Parus minor, use the ‘jar’ call in response to the presence of a snake near the nests, and the nestlings respond by escaping the nest cavity. This specific function can be observed only when nestlings are able to fledge. Do tits use the ‘jar’ call only in a situation when nestlings are physically able to jump out of the nest? We measured parental responses to live snake in 8 nests. The use of ‘jar’ call … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…While research on predator‐specific alarm calls in primates focused heavily on responses to snakes (Meno, Coss, & Perry, ; Seyfarth et al, ; Shibasaki & Kawai, ) and resulted in novel hypotheses about the effect of snake predation on the evolution of sensory and cognitive circuits in prey (Isbell, , ; Van Le et al, ), avian studies of alarm calls have relatively ignored the snake‐induced alarm vocalizations. The recent studies on the oriental tit's responses to snakes (Ha et al, ; Suzuki, , , , ; current study) suggest a new avenue of research on birds. Considering recent advances in avian phylogenetics (Prum et al, ) and cognition (Nomura & Izawa, ; Ten Cate et al, ), we propose that the ideas suggested by Isbell (Isbell, , ) and other hypotheses about the special role of snake predation in the evolution of prey can be explored and tested in studies on birds through species‐level comparisons in those avian families that include species living in regions of high snake predation or low snake predation, as well as through family‐level comparisons between families that evolutionarily originated in snake‐rich or snake‐poor regions.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…While research on predator‐specific alarm calls in primates focused heavily on responses to snakes (Meno, Coss, & Perry, ; Seyfarth et al, ; Shibasaki & Kawai, ) and resulted in novel hypotheses about the effect of snake predation on the evolution of sensory and cognitive circuits in prey (Isbell, , ; Van Le et al, ), avian studies of alarm calls have relatively ignored the snake‐induced alarm vocalizations. The recent studies on the oriental tit's responses to snakes (Ha et al, ; Suzuki, , , , ; current study) suggest a new avenue of research on birds. Considering recent advances in avian phylogenetics (Prum et al, ) and cognition (Nomura & Izawa, ; Ten Cate et al, ), we propose that the ideas suggested by Isbell (Isbell, , ) and other hypotheses about the special role of snake predation in the evolution of prey can be explored and tested in studies on birds through species‐level comparisons in those avian families that include species living in regions of high snake predation or low snake predation, as well as through family‐level comparisons between families that evolutionarily originated in snake‐rich or snake‐poor regions.…”
Section: Discussionmentioning
confidence: 63%
“…As a control group, three recordings of vocalizations of oriental turtle dove (Boesman, , ; Wulf, ) were downloaded from Xeno‐canto (Xeno‐canto Foundation). Because we already knew that the playback of dove song does not trigger fledging (Ha et al, ), it was used as a control group in case we needed to compare the responses to chipmunk playback with the responses to a neutral sound. This species is not a predator of small passerines, and we frequently heard its vocalizations in the breeding season.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations